Emerging seed enhancement technologies for overcoming barriers to restoration. (15th January 2016) - Madsen, Matthew D.; Davies, Kirk W.; Boyd, Chad S.; Kerby, Jay D.; Svejcar, Tony J.
Abstract : Rangelands occupy over a third of global land area, and in many cases are in less than optimum condition as a result of past land use, catastrophic wildfire, and other disturbances, invasive species, or climate change. Often the only means of restoring these lands involves seeding desirable species, yet there are few cost effective‐seeding technologies, especially for the more arid rangeland types. The inability to consistently establish desired plants from seed may indicate that seeding technologies being employed are not successful in addressing the primary sources of mortality in the progression from seed to established plant. Seed enhancement technologies allow for the physical manipulation and application of materials to the seed that can enhance germination, emergence, and/or early seedling growth. In this article, we examine some of the major limiting factors impairing seedling establishment in North America's sagebrush steppe ecosystem and propose seed enhancement technologies that may have the potential to overcome these restoration barriers. We discuss specific technologies for: (1) increasing soil water availability; (2) enhancing seedling emergence in crusting soil; (3) controlling the timing of seed germination; (4) improving plantability and emergence of small‐seeded species; (5) enhancing seed coverage of broadcasted seeds; and (6) protecting seedlings from pre‐emergent herbicide. Concepts and technologies in this article for restoring the sagebrush steppe ecosystem may apply generally to semiarid and arid rangelands around the globe.